Technology and American economic growth - Rosenberg, Nathan (Sharpe, 1972)
n 1982, Vaclav Smil turned upside down traditional perceptions of China as a green paradise in "The Bad Earth". Updating and expanding its basic arguments and perceptions, this volume is an inquiry into the fundamental factors, needs, prospects, and limits of modern Chinese society.